Job-Related Programs for People on Supervision: Reframing the Problem. Issue 1 (May 2022) - Bushway, Shawn
Job training programs for people under supervision have been based on an economic framework that identifies individuals involved in crime as a disadvantaged group with poor human capital. The best available research evidence has not found that these programs consistently improve employment outcomes. This article reviews the evidence for the effectiveness of standard job training programs and then examines new developments in the field that use alternative frameworks for understanding the roles of such programs. The first alternative is signaling: how people under community supervision use the completion of job training to signal to employers and others that the behavior that led to their conviction is either anomalous or no longer representative of them. The second alternative is a model of desistance known as identity change: the ways in which job training can help individuals solidify a new, more prosocial identity. I make sense of extant work and new alternatives and provide a set of recommendations for change in the community supervision system.